A qualitative and quantitative evaluation of freezing stress in wheat - Ceronio, Gert Michael (University of the Free State, 2005)
In South Africa loss of income as a result of frost damage to wheat has had far reaching consequences for the wheat industry in recent times. This is the result of early maturing wheat as well as the occurrence of late frost in early spring when wheat is most susceptible to frost damage, therefore intensifying the risk of frost stress. The objectives of this study were to: a) evaluate the quantitative and qualitative characteristics of different growth types (winter, intermediate and spring wheat) for tolerance to frost (freezing) during the tillering, flag leaf, flowering and hard dough growth stages at different sub-zero temperatures; b) evaluate different growth types for frost tolerance at different flag leaf growth stages; c) evaluate different growth types for frost tolerance at different flowering stages; and d) compile a guide with illustrations of frost injury symptoms that could be used by wheat growers and other participants in the wheat industry. a) Artificial freezing was used to evaluate the reaction response of different growth types at different temperatures (0 to –12°C with 3°C increments) and at different growth stages (tillering, flag leaf, flowering and hard dough). A quantitative evaluation showed that all cultivars were to some degree sensitive to frost damage. Cultivars 1 to 3 showed the highest degree of sensitivity at the flag leaf stage, while cultivar 4 proved to be more sensitive at the flowering stage. Though the growth stages differed in terms of sensitivity to frost stress, it was evident that temperatures below –6°C led to a reduction in growth and development, and subsequently a reduction in the parameters measured. Finally, the different genotypes had a profound influence on the reaction of wheat to frost injury, with the winter type being more tolerant than the spring type. b) A qualitative evaluation of different growth types, in terms of protein content and stirring number, was conducted at different temperatures and different growth stages. Results obtained at the different growth stages, before grain filling commenced, showed no differences. Only the hard dough stage seemed to be negatively influenced by the cumulative effect of a decrease in temperature. Generally a decrease in temperature led to a decrease in grain quality at different growth stages. c) Artificial freezing was also used to evaluate the reaction of two growth types at different temperatures (–5° to –9°C with 2°C increments) and at different flag leaf stages (early flag leaf, flag leaf and emerging of awns). The quantitative evaluation showed cultivar 1 (winter type) to be more tolerant to frost injury than cultivar 2 (intermediate type). However, both cultivars were highly sensitive to frost injury at the early flag leaf than at the flag leaf and emergence of the awns stages. Furthermore, the primary spikes were shown to sustain the highest degree of frost injury during this trial. d) During this trial the reaction response of two growth types at different temperatures (–5° to –9°C with 2°C increments) and at different flowering stages (0, 50 and 100% flowering), was evaluated. The quantitative evaluation showed cultivar 1 (winter type) to be more frost tolerant than cultivar 2 (intermediate type). At the different flowering stages both cultivars proved to be highly sensitive to frost injury at temperatures lower than –5°C. No significant differences were obtained for cultivar 1 at the different flowering stages, but cultivar 2 was more sensitive at 0% flowering than at other growth stages. e) A guide was finally compiled to assist the producer, agronomist, insurance companies and other role players in the wheat industry. This guide consists of short discussions supported by photographs to illustrate frost damage to South African wheat.

In Suid-Afrika het die verlies aan inkomste as gevolg van rypskade op koring onlangs verrykende gevolge op die koringbedryf gehad. Hierdie is die gevolg van koring wat voortydig wasdom bereik sowel as die voorkoms van laat ryp vroeg in die lente wanneer koring die gevoeligste vir rypskade is, wat gevolglik die risiko vir rypskade verhoog. Die doelstellings van die studie was om: a) die kwantitatiewe en kwalitatiewe eienskappe van verskillende koringtipes (winter, intermediêre en lente tipes) vir ryptoleransie (vriestoleransie) gedurende die stoel-, vlagblaar-, blom- en hardedeegstaduims by verskillende temperature benede vriespunt te evalueer; b) verskillende koring tipes vir ryptoleransie by verskillende vlagblaarstadiums te evalueer; c) verskillense koringtipes vir ryptoleransie by verskillende blomstadiums te evalueer; en d) ’n handleiding wat rypskade simptome illustreer saam te stel wat deur produsente en ander belanghebbendes in die koringbedryf gebruik kan word. a) ’n Kunsmatige vriesmetode is gebruik om die reaksie van verskillende koringtipes by verskillende temperature (0 tot –12°C met 3°C inkremente) by verskillende groeistadia (stoel-, vlagblaar-, blom- en hardedeegstadium) te evalueer. Al die cultivars het tydens die kwantitatiewe evaluering ’n mate van sensitiwiteit teenoor rypskade getoon. Cultivars 1 tot 3 het die hoogste graad van sensitiwiteit tydens die vlagblaarstadium getoon, terwyl cultivar 4 meer sensitief tydens die blomstadium was. Alhoewel die groeistadiums sensitiwiteitsverskille getoon het, was daar ’n duidelike aanduiding dat temperature benede –6°C tot ’n verlaging in die groei en ontwikkeling van koring gelei het en gevolglik ’n verlaging in die gemete parameters. Laastens het die verskillende koringtipes (genotipes) ’n duidelike invloed op die die reaksie van koring op rypskade uitgeoefen waar die wintertipe ’n groter mate van toleransie as die lentetipes getoon het. b) ’n Kwalitatiewe evaluering van verskillende koringtipes, in terme van proteïn-inhoud en roergetal, is by verskillende temperature en verskillende groeistadiums uitgevoer. Resultate wat vir die groeistadiums voor graanvulling het geen verskille getoon nie. Dit blyk dat slegs die hardedeegstadium negatief beïnvloed is deur die kumulatiewe effek van dalende temperature. In die algemeen het dalende temperature to die verlaging in graankwaliteit by verskillende groeistadiums gelei. c) ’n Kunsmatige vriesmetode is gebruik om die reaksie van twee koring tipes by verskillende temperature (–5 tot –9°C met 2°C inkremente) en by verskillende vlagblaarstadiums (vroeë vragblaar, vlagblaar en verskeining van angels). Tydens die kwantitatiewe evaluering het cultivar 1 (wintertipe) ’n groter mate van ryptoleransie as cultivar 2 (intermediêre tipe) getoon. Beide cultivars het ’n groot mate van sensitiwiteit tydens die vroeë vlagblaarstadium as die vlagblaar en/of aarverskyning van angels getoon. Verder het die primêre are die grootste mate van rypskade tydens die proef getoon. d) Tydens die proef is die reaksie van twee verskillende koringtipes by verskillende temperature (–5 tot –9°C met 2°C inkremente) en by verskillende blomstadiums (0, 50 en 100% blom), geëvalueer. Die kwantitatiewe evaluering het getoon dat cultivar 1 (wintertipe) meer ryptolerant as cultivar 2 (intermediêre tipe) was. By al die blomstadiums het albei cultivars ’n hoër mate van rypsensitiwiteit by temperature laer as –5°C getoon. Geen betekenisvolle verskille is vir cultivar 1 by die verskillende blomstadiums gevind nie, maar cultivar 2 het ’n hoër mate van sensitiwiteit by 0% blom as die ander blomstadiums getoon. e) ’n Handleiding is saamgestel as hulpmiddel wat deur produsente, agronome, versekerings-instansies en ander rolspelers in die koringindustrie gebruik kan word. Die handleiding bestaan uit bondige besprekings wat deur foto’s ondersteun word om rypskade op Suid-Afrikaanse koring te illustreer.
Thesis (Ph.D. (Soil, Crop and Climate Sciences))--University of the Free State, 2005
Keywords: Wheat; Frost; Freezing; Temperature; Growth stage; Flag leaf; Flowering; Yield components; Protein; Symptoms; Wheat -- Breeding -- South Africa; Wheat -- Frost resistance -- South Africa